Fuzzy adaptive control for the actuators position control and modeling of an expert system - Soyguder, Servet; Alli, Hasan (Pergamon-Elsevier Science Ltd, 2010)
In this paper, a heating, ventilating and air-conditioning (HVAC) system was designed and two different damper gap rates (actuators position) of the HVAC system were controlled by a conventional PID (proportional-integral-derivative) controller. One of the dampers was controlled by using the required temperature for the interested indoor volume while the other damper was controlled by using the required humidity for the same indoor volume. The realized system has a zone with variable flow-rate by considering the ambient temperature and humidity. The required air flow was supplied by controlled of the dampers placed on the entrance ducts of indoor, Programmable Logic Controller (PLC) used PID control algorithm was utilized to control the system. This system has been controlled by a PLC based closed-loop controller. In this work, the realized system has been controlled by PLC used PID control algorithm. The optimal values of PID parameters were obtained by using Fuzzy sets. Fuzzy adaptive control has been performed to maximize the performance of the system. Efficiency of fuzzy adaptive control (FAC) developed method was successfully obtained. (C) 2009 Published by Elsevier Ltd.
Keywords: Fuzzy adaptive control (FAC); Modeling; Actuator position control; Air flow control; PID control; Humidity control; Software architecture; An expert system